Storage stability of hydrolyzed palm kernel oil and red palm super olein blend and its softgel capsule - Mulyono, Manda Edy; Rizki, Ilmi Fadhilah; Panjaitan, Frisda Rimbun; Bajra, Brahmani Dewa (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2025)
Hydrolyzed palm kernel oil (PKO) and red palm super olein (RPSO) blend, known as HPRB, is a novel product with potential benefits for digestive health. This blend combines the antimicrobial properties of hydrolyzed PKO with the antioxidant effects of RPSO. However, the long-term stability of HPRB under different storage conditions is crucial to ensure its efficacy and safety. This study aims to evaluate the storage stability of HPRB in its oil form and as a softgel capsule. The research investigated the impact of various storage conditions on the phytonutrient content, fatty acid composition, and acylglycerol profile of HPRB. The results showed that cool and dark storage conditions best preserve the phytonutrient content of HPRB. The fatty acid and acylglycerol compositions of HPRB remained stable regardless of the storage conditions. Accelerated stability testing of HPRB softgel capsules demonstrated excellent stability across various parameters, including physical characteristics, microbiological quality, and chemical stability. Shelf-life estimation indicated a relatively long shelf life for the softgel capsules under accelerated conditions. These results suggest that HPRB, particularly when stored appropriately or encapsulated in softgel form, has the potential for long-term stability and safe use.